Indoxyl-based umpolung strategy for the synthesis of unsymmetrical 3, 3′-biindoles. Issue 49 (7th December 2016) - Guo, Jing; Weng, Jiang; Huang, Gong-Bin; Huang, Lin-Jie; Chan, Albert S.C.; Lu, Gui
Graphical abstract: Highlights: A novel indoxyl-based approach for the synthesis of unsymmetrical 3, 3′-biindoles. Broad substrate scope, good to excellent yields (24 new compounds, up to 98% yield). Mild reaction conditions: metal-free; iodine-catalyzed reactions; operational simplicity. Abstract: 3, 3′-Bisindoles are known to be important structural motifs found in bioactive natural products, pharmaceuticals, and functional materials. Herein, a novel indoxyl-based approach was established for the synthesis of unsymmetrical 3, 3′-biindoles from indoles and indoxyls. This approach generated moderate to excellent yields of the desired products (24 examples, up to 98% yield). The present method features broad substrate scope, operational simplicity, high atom economy, and utilization of non-toxic and inexpensive molecular iodine as catalyst. The applicability of this method has been demonstrated by the facile gram-scale synthesis.